Dynamics evolution and well type optimization of deep well injection in coal mines water - Longfei FENG; Shuangming WANG; Hao WANG (Meitan xuebao, 2025)
Some coal mines in the Ordos Basin face challenges in disposing of highly mineralized mine water. Deep-well reinjection technology offers an effective solution for large-scale, low-cost water management. Using a deep-well reinjection project in an Ordos mine as a case study, this research employs numerical simulations based on thermal-hydraulic-mechanical (THM) coupling governing equations to investigate the spatiotemporal evolution of reinjection flow rates and pore water pressure in target layers under varying branch numbers and well spacings in multi-lateral well systems. A theoretical model for flow rate and drawdown in inclined boreholes was developed, and a functional relationship between well spacing and flow rate was fitted for multi-lateral wells. By integrating well construction lengths, a relative cost function per unit reinjection flow rate was established, and a methodology for optimizing well configuration and spacing was proposed. Key findings include: ① Multi-lateral wells exhibit significantly higher reinjection capacities than vertical wells, with flow rates increasing with branch numbers but decaying logarithmically over time and stabilizing after approximately 1,000 days. ② Reinjection flow rates in multi-lateral systems are jointly controlled by branch numbers and well spacing. The fitted well spacing-flow rate function (R2 = 0.98) reveals that flow rates initially increase with spacing and stabilize beyond critical thresholds. For a branch inclination of 5°, flow rates stabilize when spacings exceed 200, 300, 400 m for two, three, and four-branch wells, respectively. ③ Relative construction cost per unit flow rate is proportional to well spacing. Costs escalate more rapidly with additional branches under fixed spacing. Sharp cost increases occur when maximum flow rates exceed 145, 220, 305 m3/h for two, three, and four-branch systems, respectively. ④ An optimization method for determining branch numbers and spacing was proposed, prioritizing cost efficiency. For a 5° branch inclination: Two-branch wells are optimal for flow rates between 77−149 m3/h; Three-branch wells are preferred for flow rates between 149−201 m3/h. Four-branch wells are recommended for flow rates between 201−306 m3/h. The research results provided a scientific basis for the design of mine water geological storage engineering.